Health claims: omega-3 fatty acids and cardiovascular disease - Leaf, A. (Harvard University, Boston, MA) (Nutrition reviews, 1992)
This article begins with a statement by Dr. Alexander Leaf, Emeritus Professor and former Chair of Preventive Medicine of Harvard University, who has addressed the issue of omega-3 fatty acids and their benefits in lessening cardiovascular risk. Leaf takes issue with the interpretation of the existing data made by the FDA on several important points. These points are discussed in detail